Unraveling the Meaning of Faith in the Era of Digitalization: A Literature Study of the Religious Evolution of the Post-Millennial Generation - Ali, Muhdi; Al Ayubi, Sholahuddin; Sa’ad, Suadi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
The digitalization of society has become the main catalyst for the transformation of the religious beliefs of Generation Z, who grew up in an era of rapid technological and information progress. This article examines the impact of digital interactions on Generation Z's religious understanding and behavior, with a particular focus on how this group accesses, understands, and articulates their beliefs. A qualitative approach based on a literature review reveals that Generation Z tends to adapt traditional religious values to a digital context, thereby forming a more inclusive and personal religious identity. This generation tends to favor pragmatic, results-oriented spiritual practices, allowing for a more flexible approach to religious exploration. Social media plays an important role in accessing information and building communities related to religion, although social media can also present challenges such as misinformation. As a result, understanding faith in the digital era is becoming increasingly complex, requiring individuals to have strong digital literacy to navigate the diversity of available religious information and build authentic spiritual interpretations in the context of their modern lives.